Peningkatkan Keterampilan Menulis Teks Carita Pondok Naratif dalam Pembelajaran Bahasa Sunda dengan Pendekatan Contekstual Teaching and Learning (CTL) di Kelas X SMK Pelita Alam Kota Bekasi - Amitania Ibmianur (Medan Resource Center, 2023)
The results of the study evaluation for class X students in semester 2 of SMK Pelita alam in 2021 or the 2020/2021 academic year show that students' ability to write narrative